Dinamika Wawasan Demokrasi : “Integrasi Nasional Dan Tantangan Membentuk Warga Negara Yang Berwawasan” - Neila Kholilatus Tsania; Talitha Lutfi Buchari; Suci Anugrah Tryana Hikmah; Nisrina Raudhah; Maulia Depriya Kembara (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
Democracy, national spirit and integration are the three main pillars that form the foundation for Indonesia's progress. However, unfortunately, the younger generation in the country feels that these three pillars are still not optimally implemented. In this paper, we will discuss young people's views on democracy, national spirit and integration in Indonesia. Our paper uses a qualitative research approach by interviewing 24 respondents, consisting of university students and high school students. From the interviews, the young generation expressed their concern about the condition of democracy, national spirit, and integration in Indonesia. They considered that democracy in Indonesia has not yet achieved the expected goals, as there are still widespread cases of corruption, inequality, and intolerance. Meanwhile, the importance of improving the national spirit through better education and character building was recognized. Integration in the country is also hampered by the still rampant issues of racism and intolerance. To strengthen democracy, national spirit, and integration, the young generation recommends that more serious efforts be made in the areas of education, law enforcement, and inter-group dialog. Only through these concrete measures can Indonesia achieve the goal of authentic democracy and strengthen the national spirit and integration in a diverse society.